Ergonomics-Based Redesign of Tourist Boat Stairs Using a Quality Function Deployment (QFD) Approach to Improve Traveler Security and Comfort - Hidayatullah, Rizki; Kurnia, Fikrihadi; Suartika, I Made; Kaliwantoro, Nur (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
This research aims to redesign an ergonomic tourist boat ladder to improve the comfort and safety of tourists in the context of marine tourism. Tanjung Luar Tourism Village, East Lombok, was chosen as the research location due to the high potential of tourists using boats as a means of transportation to marine tourism destinations. Currently, many tourist boats are not equipped with safe and comfortable stairs, increasing the risk of accidents. The method used in this research is Quality Function Deployment (QFD), which identifies the needs and preferences of tourists through surveys and questionnaires. The research sample consisted of 57 respondents, including tourists, boat crew, and ergonomics experts. The House of Quality (HoQ) results showed that the main needs of tourists include comfortable and safe handrails, anti-slip stair surfaces, and corrosion-resistant stair materials. Based on these needs, three alternative boat ladder designs were developed that consider aspects of safety, durability, and ease of use in marine environmental conditions. Products with ergonomic handrails, stainless steel material, and design flexibility were prioritized in the development. These designs are expected to not only provide a safer and more comfortable solution for users but also contribute to the development of safety standards for tourist boats in Indonesia. This research provides a foundation for the improvement of tourist boat facilities, especially in areas with great potential in marine tourism.